Studies on Nonconventional Oil Seeds: A New Source of Edible and Industrial Oils - Mondhe, OP.S.; Rao, J.T. (Asian Journal of Chemistry, 2010)
The seeds of Pithecellobwm dulce belonging to Leguminoseae family obtained from forest origin were examined for their fatty oil constituents and some applications of oils to edible as well as industrial purposes.